2021
DOI: 10.3892/etm.2021.9756
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA small nucleolar RNA host gene 1 knockdown suppresses the proliferation, migration and invasion of osteosarcoma cells by regulating microRNA‑424‑5p/FGF2 in vitro

Abstract: The aim of the present study was to clarify the effect of long non-coding RNA (lncRNA) small nucleolar RNA host gene 1 (SNHG1) on the proliferation, migration and invasion of osteosarcoma (OS) cells and to explore the potential underlying mechanisms. The expression levels of SNHG1, microRNA (miR)-424-5p and fibroblast growth factor 2 (FGF2) in OS tissues and cells were detected using reverse transcription-quantitative polymerase chain reaction. OS cell proliferation, migration and invasion were analysed by MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…SNHG1 was upregulated in OS tissues and promoted cell proliferation, invasion, and migration by serving as a ceRNA. 38 40 Highly expressed SNHG6 was positively associated with poor overall survival of patients with OS and could enhance OS cell proliferation by regulating the miR-26a-5p/ULK1 axis and expression of p21 and Kruppel-like factor 2 (KLF2). 41 , 42 It has been reported that SNHG7 was aberrantly expressed in OS tissues and elevated levels of SNHG7 could facilitate tumor growth and epithelial-mesenchymal transition (EMT) by regulating p53 expression and miR-34a levels.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG1 was upregulated in OS tissues and promoted cell proliferation, invasion, and migration by serving as a ceRNA. 38 40 Highly expressed SNHG6 was positively associated with poor overall survival of patients with OS and could enhance OS cell proliferation by regulating the miR-26a-5p/ULK1 axis and expression of p21 and Kruppel-like factor 2 (KLF2). 41 , 42 It has been reported that SNHG7 was aberrantly expressed in OS tissues and elevated levels of SNHG7 could facilitate tumor growth and epithelial-mesenchymal transition (EMT) by regulating p53 expression and miR-34a levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nine members of the family have been also reported to drive osteosarcomagenesis through different ceRNETs (Table 1 ). Among them, SNHG1 is consistently reported to be upregulated in OS tissues and cells, correlated with tumor size, TNM stage and lymph node metastasis, predicting poor overall survival [ 162 165 ]. In particular, the lncRNA is able to promote proliferation, migration, tumor growth and metastasis, as demonstrated in vitro and in vivo experiments through the ceRNA activity involving the miR-326/NOB1, miR-493/S100A6 and miR-577/Wnt2B axes, with the last one also activating the Wnt/beta-catenin signal pathway, one of the most critical pathway relevant for both cell proliferation and metastasis [ 162 164 ].…”
Section: Cernets Involving Lncrnasmentioning
confidence: 99%
“…For evaluation of their relation to miR-424, following studies have been conducted: In osteosarcoma cell lines Saos-2, MG63, HOS and U2OS, SNHG1 acts as a molecular sponge for miR-424-5p. After knocking down SNHG1, expression levels of miR-424-5p rises and this miRNA can target 3′-UTR of FGF2, resulting in reduced proliferation, migration and invasion [ 16 ]. The same molecular mechanism also applies for cervical cancer cells, but the difference is that sponging molecule is SNHG12 in this case and there is no FGF2 targeting [ 17 ].…”
Section: Cancer Cell Linesmentioning
confidence: 99%